SIGI TENTANG PENGGUNAAN MEDIA PEMBELAJARAN PADA MATA DIKLAT PRODUKTIF AKUNTANSI DI KELAS X AKUNTANSI DI SMK NEGERI 4 SURABAYA - EVRIN CHRISTIANA (Program Studi Pendidikan Akuntansi Fakultas Ekonomika dan Bisnis Universitas Negeri Surabaya, 2013)
Learning resources such as learning media is supporting the achievement of learning objectives because with the development of technology, teachers can utilize technology as a tool that makes it easier in the delivery of learning materials to learners. Therefore, it is necessary to use media holding torch of learning which aims to determine the instructional media used, reasons for use of instructional media, along with the feasibility study media used by the teacher.Types of research is descriptive research with quantitative approach. Data collection techniques using the documentation, interviews, and questionnaires covered. The results of the feasibility study of instructional media were analyzed using a Likert scale. Based on the research that teachers use the instructional media in the form of powerpoint SMK Negeri 4 citing effectiveness and time effectiveness, effort, and cost.Results of the data processing are processed indicates that the feasibility of media power point that is used by the accounting class X Accounting in SMK Negeri 4 Surabaya feasibility-namely the eligibility criteria ≥ 75% (decent). Keywords: Feasibility, Media learning